Formulasi Kebijakan: Tahap Agenda Setting Pendirian Sekolah Menengah Pertama Negeri di Kota Batu - Dody Setyawan; Firman Firdausi (Universitas Muhammadiyah Mataram, 2021)
The vision and mission of the Regional Head is one of the keys to the success of development in this city. One aspect that is of concern to the government is education as a form of human resource development. Zoning has an impact on the affordability of students to schools, especially public schools. This indirectly affects the capacity of the school. This study aims to determine the urgency of developing junior high school (called SMP) infrastructure with state status in the agenda setting stage. This research using mixed methods and interactive model data analysis. Interactive data analysis are popularized by Miles, Huberman and Saldana (2014), the result is that the infrastructure development of public junior high schools is needed, especially in areas affected by zone-political.